Melakukan Penelitian Tindakan Kelas - Agung Prihantoro; Fattah Hidayat (Universitas Cokroaminoto Yogyakarta, 2019)
The paper explores the classroom action research as one of research methodologies. This kind of research methodology aims to solve learning and teaching problems and improve the quality of education. There are four models of classroom action research, namely Kurt Lewin model, Stephen Kemmis and Robyn McTaggart model, Margaret Riel model, and Robert P. Pelton model. To make the models easy to apply, the authors show an example of classroom action research framework.